Helicobacter pylori in First Nations and Recent Immigrant Populations in Canada. (2012) - Jones, Nicola L; Chiba, Naoki; Fallone, Carlo; Thomson, Alan; Hunt, Richard; Jacobson, Kevan; Goodman, Karen
Abstract : The diminishing prevalence of Helicobacter pylori infection among most segments of the Canadian population has led to changes in the etiologies and patterns of associated upper gastrointestinal diseases, including fewer peptic ulcers and their complications. Canadian Aboriginals and recent immigrants are among populations in which the prevalence of H pylori infection remains high and, therefore, the health risks imposed by H pylori remain a significant concern. Population-based strategies for H pylori eradication in groups with a low prevalence of infection are unlikely to be cost effective, but such measures are attractive in groups in which the prevalence rates of infection remain substantial. In addition to a lower prevalence of peptic ulcers and dyspepsia, the public health value of eradication may be particularly important if this leads to a reduction in the prevalence of gastric cancer in high prevalence groups. Therefore The Canadian Helicobacter Study Group held a conference that brought together experts in the field to address these issues, the results of which are reviewed in the present article. Canadians with the highest prevalence of H pylori infection are an appropriate focus for considering the health advantages of eradicating persistent infection. In Canadian communities with a high prevalence of both H pylori and gastric cancer, there remains an opportunity to test the hypothesis that H pylori infection is a treatable risk factor for malignancy.